ANALYSIS AND PRACTICAL COMPARISON OF PACKET FILTRATION ALGORITHMS - Rakhmankulova, Mashhura; Gulamov , Sherzod (Techscience uz - Topical Issues of Technical Sciences, 2025)
Packet classification is one of the important components of network tools, such as firewalls and routers. All packages must be systematically classified, which facilitates the provision of broadband Internet services, as well as support for various applications such as Internet games, Video on Demand (VoD), TV/Radio, and e-businesses. These applications constantly require high bandwidth, stringent Quality of Service (QoS) requirements, and complex security measures. This article presents an evaluation and analysis of BV, HiCuts packet classification algorithms, each of which is based on a decision tree structure. Evaluations were carried out in procedures based on similar principles and design choices. Performance indicators were obtained by applying the implemented classifiers to the test medium under the same conditions. The main goal is to ensure unbiased comparison of two classification algorithms with the same criteria and evaluation cases. This work focuses on the evaluation of high-performance packet classification systems, as they are necessary to combat security risks in future routers and transfer systems.